2015
DOI: 10.1007/s00268-015-3108-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Central Compartment Lymph Node Metastasis in Papillary Thyroid Microcarcinoma: A Meta‐Analysis

Abstract: Prophylactic CLND may be performed in PTMC patients with clinically uninvolved central lymph nodes but with high risk factors; multicenter studies with long-term follow-up are recommended to better understand the risk factors and surgical management for central nodes in PTMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
55
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 46 publications
17
55
4
1
Order By: Relevance
“…Male sex was a risk factor for LNM, which suggests that males require specialized neck checkups of the thyroid to enable the early detection of thyroid tumors 15. Patient age is known to be an important risk factor for patients with PTC >1 cm;31,32 our results indicated that younger age (<45 years) was associated with an increased risk of LNM in PTMC patients.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Male sex was a risk factor for LNM, which suggests that males require specialized neck checkups of the thyroid to enable the early detection of thyroid tumors 15. Patient age is known to be an important risk factor for patients with PTC >1 cm;31,32 our results indicated that younger age (<45 years) was associated with an increased risk of LNM in PTMC patients.…”
Section: Discussionmentioning
confidence: 59%
“…On the other hand, given the potentially high prevalence of LNM in PTMC, some authors agree that prophylactic lymph node dissection (LND) permits an improved staging of the disease that may guide subsequent treatment;14 however, few studies have demonstrated a meaningful role of prophylactic LND in relation to locoregional control or survival in PTMC. A systematic review that included 8,345 PTMC patients explored the risk factors associated with central lymph node metastasis (CLNM) and proposed that prophylactic central lymph node dissection (CLND) should be considered in PTMC patients with risk factors 15. However, the deficiency of long-term follow-up data for the analysis was a limitation in that study.…”
Section: Introductionmentioning
confidence: 99%
“…To date, five meta‐analyses have been performed to identify the clinical risk factors for central neck lymph node metastases (CLNM) in PTC and papillary thyroid microcarcinoma (PTMC). These meta‐analyses found association between CLNM and several clinicopathological factors, including age, sex, tumor size, multifocality, tumor location, lymphovascular invasion, extrathyroidal extension (ETE), and lymphocytic thyroiditis . Two meta‐analysis also found that CLNM is associated with lateral neck lymph node metastasis (LLNM) .…”
Section: Introductionmentioning
confidence: 93%
“…[3] Tumor location has been shown to be associated with neck metastasis. [4] There has been some interest in specific cases with rare locations and high biological activity, such as PTCs located in the isthmus, those with multiple foci and those with local invasion to adjacent tissues. [5] The thyroid isthmus lies directly anterior to the trachea, overlying the second to fourth tracheal rings and covered by the strap muscles, fascia and skin in the middle of the neck.…”
Section: Introductionmentioning
confidence: 99%